Combined Functional Genome Survey of Therapeutic Targets for Hepatocellular Carcinoma - Reiko Satow; Miki Shitashige; Yae Kanai; Fumitaka Takeshita; Hidenori Ojima; Takafumi Jigami; Kazufumi Honda; Tomoo Kosuge; Takahiro Ochiya; Setsuo Hirohashi; Tesshi Yamada (2010)
The outcome of patients with advanced hepatocellular carcinoma (HCC) has remained unsatisfactory. Patients with HCC suffer from chronic hepatitis or liver cirrhosis, and their reserve liver function is often limited.To develop new therapeutic agents that act specifically on HCC but interfere only minimally with residual liver function, we searched for genes that were upregulated in 20 cases of HCC [namely, discovery sets 1 (n = 10) and 2 (n = 10)] in comparison with corresponding nontumorous liver and a panel representing normal organs using high-density microarrays capable of detecting all exons in the human genome.Eleven transcripts whose expression was significantly increased in HCC were subjected to siRNA-based secondary screening of genes required for HCC cell proliferation as well as quantitative reverse transcription-PCR analysis [validation sets 1 (n = 20) and 2 (n = 44)] and immunohistochemistry (n = 19). We finally extracted four genes, AKR1B10, HCAP-G, RRM2, and TPX2, as candidate therapeutic targets for HCC. siRNA-mediated knockdown of these candidate genes inhibited the proliferation of HCC cells and the growth of HCC xenografts transplanted into immunodeficient mice.The four genes we identified were highly expressed in HCC, and HCC cells are highly dependent on these genes for proliferation. Although many important genes must have been overlooked, the selected genes were biologically relevant. The combination of genome-wide expression and functional screening described here is a rapid and comprehensive approach that could be applied in the identification of therapeutic targets in any type of human malignancy.